TEACHING WRITING SKILL IN DESCRIPTIVE TEXT THROUGH GUIDED QUESTIONS TO THESEVENTH GRADE STUDENTS OF TAMAN DEWASA IBU PAWIYATAN YOGYAKARTA - Ningtyas, Dwi Ambaretno (Universitas Bandar Lampung, 2018)
This study is aimed to find out how the teachers improve the students‟ ability in writing especially in writing text by using guided question. This study is a case study. The subject of the research is 25 students of seven C graders of SMP Taman Dewasa Ibu Pawiyatan Yogyakarta. The research consists of four steps; observing in pre-test, observing in post-test 1, observing in post-test 2, and observing in post-test 3. The data were in the form of the observation from the result of pre-test, observing in post-test 1, observing in post-test 2, and observing in post-test 3. The finding of the study indicated that the students can make a text descriptive automatically by using guided questions. The students can make a text description with easy by using guided question and the students‟ ability in writing especially descriptive text was increased by using guided questions.